Penerapan Model Pembelajaran Contextual Teaching and Learning pada Mata Pelajaran PAI untuk Membentuk Karakter Cinta Damai di Sekolah Dasar Pelita Kota Bandung - 10030121114, Dina Nurdiana; Eko Surbiantoro; Dewi Mulyani (UNISBA Press, 2025)
Abstract. In an attempt to help students at Pelita Elementary School in Bandung City develop peaceful dispositions, this study will investigate how the Contextual Teaching and Learning (CTL) model is applied in Islamic Religious Education (PAI) courses. Data for this study was gathered by observation, interviews, and recording using a qualitative descriptive method. The study's findings demonstrate that using the CTL model can help students better comprehend the importance of cooperation, tolerance, and amicable dispute resolution. Numerous elements, including teacher preparation, school support, and student participation in the learning process, contribute to this model's success. However, this study also identifies obstacles, including limited facilities and differences in students' initial understanding of the concept of peace-loving. This study recommends strengthening the implementation of CTL through training for teachers and the integration of peace-loving values in a more comprehensive curriculum.Keyword: Contextual Teaching and Learning, Islamic Religious Education, Peace-loving Character, Elementary School Abstrak. Dalam upaya membantu anak-anak di Sekolah Dasar Pelita di Kota Bandung mengembangkan karakter cinta damai, penelitian ini akan melihat bagaimana pendekatan Pembelajaran Kontekstual (CTL) diterapkan dalam mata kuliah Pendidikan Agama Islam (PAI). Penelitian ini menggunakan metodologi deskriptif kualitatif yang mengumpulkan data melalui dokumentasi, wawancara, dan observasi. Temuan penelitian menunjukkan bahwa penggunaan model CTL dapat membantu peserta didik lebih memahami nilai-nilai kerjasama, toleransi, dan penyelesaian sengketa secara damai. Keberhasilan model ini didukung oleh berbagai faktor, seperti dukungan sekolah, pelatihan guru, dan keterlibatan aktif peserta didik dalam proses pembelajaran. Meski demikian, penelitian ini juga mengidentifikasi kendala, antara lain keterbatasan fasilitas serta perbedaan pemahaman awal peserta didik tentang konsep cinta damai. Penelitian ini merekomendasikan penguatan pelaksanaan CTL melalui pelatihan bagi guru dan integrasi nilai cinta damai dalam kurikulum yang lebih komprehensif.Kata Kunci: Contextual Teaching and Learning, Pendidikan Agama Islam, Karakter Cinta Damai, Sekolah Dasar